Pengaruh PDRB Sektor Migas dan Tenaga Kerja terhadap Kemiskinan di Kabupaten Bojonegoro - Fitriana, Annisa Nur; Cahyono, Hendry (Jurnal Ekonomika : INDEPENDEN, 2023)
The objective of this study is to investigate the impact of the oil and gas industry's gross regional domestic product and labor on poverty levels in the Bojonegoro district from 2000 to 2021. The variables under investigation in this study include poverty as the dependent variable, and gross regional domestic product and labor as independent variables. The present study employs a quantitative research design and utilizes the multiple linear regression analysis technique with OLS (Ordinary Least Square) as the chosen method of analysis. The findings indicate that the gross regional domestic product of the oil and gas industry, as well as labor, exert a noteworthy impact on poverty levels in the Bojonegoro district during the period spanning from 2000 to 2021.